The opsin repertoire of the Antarctic krill Euphausia superba - Biscontin, Alberto; FRIGATO, Elena; Sales, Gabriele; Mazzotta, Gabriella M.; Teschke, Mathias; De Pittà, Cristiano; Jarman, Simon; Meyer, Bettina; Costa, Rodolfo; BERTOLUCCI, Cristiano (Marine Genomics, 2016)
The Antarctic krill Euphausia superba experiences almost all marine photic environments throughout its life cycle. Antarctic krill eggs hatch in the aphotic zone up to 1000. m depth and larvae develop on their way to the ocean surface (development ascent) and are exposed to different quality (wavelength) and quantity (irradiance) of light. Adults show a daily vertical migration pattern, moving downward during the day and upward during the night within the top 200. m of the water column. Seawater acts as a potent chromatic filter and animals have evolved different opsin photopigments to perceive photons of specific wavelengths. We have investigated the transcriptome of E. superba and, using a candidate gene approach, we identified six novel opsins. Five are r-type visual opsins: four middle-wavelength-sensitive (EsRh2, EsRh3, EsRh4 and EsRh5) and one long-wavelength-sensitive (EsRh6). Moreover, we have identified a non-visual opsin, the EsPeropsin. All these newly identified opsin genes were significantly expressed in compound eyes and brain, while only EsPeropsin and EsRh2 were clearly detected also in the abdomen. A temporal modulation in the transcription of these novel opsins was found, but statistically significant oscillations were only observed in EsRrh3 and EsPeropsin. Our results contribute to the dissection of the complex photoreception system of E. superba, which enables this species to respond to the daily and seasonal changes in irradiance and spectral composition in the Southern Ocean.